Gender, Agricultural Production, and the Theory of the Household - Udry, Christopher (Journal of Political Economy, 1996)
Virtually all models of the household assume that the allocation of resources is Pareto efficient. Within many African households, agricultural production occurs on many plots controlled by different members of the household. Pareto efficiency implies that factors should be allocated efficiently across these plots. I find, in contrast, that plots controlled by women are farmed much less intensively than similar plots within the household controlled by men. The estimates imply that about 6 percent of output is lost because of inefficient factor allocation within the household. The paper suggests a new approach to modeling intrahousehold allocation consistent with the empirical results.